Litewskie obchody stulecia urodzin Czesława Miłosza - Dalecka, Teresa (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
On June 27–28, the Institute of Lithuanian Literature and Folklore and the Vilnius University organized an international conference “Times and Places of Czeslaw Milosz“. The one hundredth anniversary of the birth of Czesław Milosz (1911–2004), Nobel Prize winner and alumnus of the Vilnius University, provided an important opportunity to reflect on the influence that this writer and his work had on the modern consciousness. The places of Czesław Milosz, which in his poetry served as the key guidelines in search of reality and meaning, included Lithuania, Poland, Central and Eastern Europe, France and the United States of America.